IMPLEMENTASI ETIKA BISNIS ISLAM PADA PELAKU USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) SEKTOR KULINER DI KAWASAN WISATA TANJUNG ENIM - Tiara Nabila Aulia; Said Abdullah Syahab; Safitri Asrol (Jurnal Ekonomi dan Bisnis Nias Selatan, 2026)
Islamic business ethics served as a moral guideline that directed business actors to conduct economic activities honestly, fairly, and responsibly in accordance with Islamic principles. The implementation of Islamic business ethics was particularly important in the culinary Micro, Small, and Medium Enterprises (MSMEs) sector, especially in tourism destinations where interactions between business owners and consumers were highly intensive. This study aimed to examine the implementation of Islamic business ethics among culinary MSMEs operating in the Tanjung Enim tourism area, Muara Enim Regency. A qualitative approach with a field research design was employed. The study involved 12 culinary MSME owners selected through purposive sampling. Data were collected through interviews, observations, and documentation and were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicated that the MSME owners had implemented the principle of tawhid through religious observance and the use of halal ingredients, the principle of equilibrium through honesty in pricing and service delivery, the principle of free will through business innovation that remained consistent with Islamic values, and the principle of responsibility through their willingness to accept customer feedback and address complaints. Nevertheless, the implementation had not yet been fully optimized due to several challenges, including the absence of halal certification, inadequate hygiene standardization, inconsistent measurement practices, and limited business record-keeping. The study underscored the need for strengthened guidance and assistance programs based on Islamic business ethics to enhance the competitiveness and sustainability of culinary MSMEs in tourism destinations.